Descriptions Of The Advertisement Calls Of Some Bornean Frogs - Sukumaran, J.; Das, I.; Haas , A. (Folium Publishing Company, 2010)
We describe the temporal and spectral properties of advertisement calls of seven species of Bornean anuran amphibians, from the following families—Bufonidae: Ansonia leptopus (Günther, 1872) and Ingerophrynus quadriporcatus (Boulenger, 1887); Microhylidae: Microhyla borneensis Parker, 1928; Ranidae: Hylarana signata (Günther, 1872); Megophryidae: Leptobrachella mjobergi Smith, 1925, Leptolalax cf. gracilis (Günther, 1872), and Leptolalax maurus Inger, Lakim, Biun et Yambun, 1997. All, except L. gracilis, were unreported in the literature before. For this species and for Leptobrachella mjobergi, we suspect the presence of ultrasonic component in the call, recently reported in several species of frogs from China and Borneo.